3D LIF/Mie planar droplet sizing in IC engine sprays using single-droplet calibration data - Kögl, Matthias; Mishra, Yogeshwar Nath; Hofbeck, Bernhard; Baderschneider, Kevin; Huber, Franz; Pracht, Jonas; Berrocal, Edouard; Zigan, Lars; Will, Stefan (ICLASS 2018: 14TH INTERNATIONAL CONFERENCE ON LIQUID ATOMIZATION & SPRAY SYSTEMS, 2018)

3D LIF/Mie planar droplet sizing in IC engine sprays using single-droplet calibration data - Kögl, Matthias; Mishra, Yogeshwar Nath; Hofbeck, Bernhard; Baderschneider, Kevin; Huber, Franz; Pracht, Jonas; Berrocal, Edouard; Will, Stefan; Zigan, Lars (ICLASS 2018 - 14th International Conference on Liquid Atomization and Spray Systems, 2020)
This paper reports on the quantitative 2D and 3D droplet sizing based on the LIF/Mie ratio in ethanol DISI (Direct Injection Spark Ignition) sprays, where the required calibration is performed using quantitative micro and macro LIF/Mie ratio imaging of individual microdroplets. The droplets are generated from a monodisperse droplet generator in a diameter range from 16 µm to 60 µm. First, the liquid LIF (laser-induced fluorescence) and Mie scattered light (Mie) intensity from the dye-doped ethanol droplet illuminated by the 532 nm laser sheet are simultaneously recorded using a microscopic and a macroscopic imaging objective. The light intensity of the LIF and Mie optical signals are evaluated as a function of droplet diameters (d). The LIF and Mie intensity is found in a good agreement with volumetric (d3) and surface (d2) dependencies, respectively. Both micro and macro LIF/Mie intensity ratio show a linear dependence on d. The deduced calibration curve showing a correlation between LIF/Mie intensity ratio and droplet diameter is then used for the calibration of LIF/Mie ratio for 3D droplet size (Sauter Mean Diameter: SMD) in sprays. For 3D sizing, two-phase SLIPI-(Structured Laser Illumination Planar Imaging) based droplet sizing is applied in combination with laser sheet scanning for probing the spray in several two-dimensional (2D) slices. These 2D layers are combined together to reconstruct a quantitative 3D map of droplet SMD. Droplet SMD in the spray is found in the range between 10 µm and 50 µm.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Direct-injection spark ignition (DISI); Ethanol; Laser-induced fluorescence; Mie scattering; SLIPI